2022
DOI: 10.1016/j.ajo.2021.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Degree of Myopia and Glaucoma Risk: A Dose-Response Meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 60 publications
2
51
0
2
Order By: Relevance
“…A study from Korea found a positive trend between increased myopic refractive error and POAG prevalence ( 70 ). Recently, a meta-analysis by Ahnul Ha et al corroborated this finding: every diopter in myopia increases the risk of glaucoma by ~20% ( 71 ). Thus, high myopia is now regarded as a risk factor for glaucoma ( 72 74 ).…”
Section: Discussionmentioning
confidence: 88%
“…A study from Korea found a positive trend between increased myopic refractive error and POAG prevalence ( 70 ). Recently, a meta-analysis by Ahnul Ha et al corroborated this finding: every diopter in myopia increases the risk of glaucoma by ~20% ( 71 ). Thus, high myopia is now regarded as a risk factor for glaucoma ( 72 74 ).…”
Section: Discussionmentioning
confidence: 88%
“…Diabetes mellitus has already been suggested to increase the risk of OAG [21,22], because higher serum glucose levels are associated with high intraocular pressure, which is thought to result in optic nerve damage [23]. Myopia, especially high myopia, has been reported as a major risk factor for OAG [24,25]. This is further supported by the Tajimi study conducted in Japan, which also showed an association between myopia and glaucoma [4].…”
Section: Discussionmentioning
confidence: 92%
“…Ha et al assessed the association between myopia and open-angle glaucoma risk by dose-response meta-analysis and reported that the risk of glaucoma increased more steeply with decreasing spherical equivalent from approximately −6 diopters, and increased more steeply from −8 diopters [ 20 ]. The majority of epidemiological studies used in the meta-analysis were not analyzed by OCT, and glaucomatous optic atrophy was determined based on fundus photographs and visual field testing.…”
Section: Discussionmentioning
confidence: 99%